Guidelines of the Russian gastroenterological association and Russian Association of Coloproctology on diagnostics and treatment of ulcerative colitis in adults - V. T. Ivashkin; Yu. A. Shelygin; D. I. Abdulganiyeva; R. A. Abdulkhanov; O. P. Alekseeva; S. I. Achkasov; A. Yu. Baranovsky; Ye. A. Belousova; O. V. Golovenko; Ye. G. Grigor'yev; N. V. Kostenko; T. L. Lapina; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.